Mapping tree species vulnerability to multiple threats as a guide to restoration and conservation of tropical dry forests - Fremout, Tobias; Thomas, Evert; Gaisberger, Hannes; Meerbeek, Koenraad van; Muenchow, Jannes; Briers, Siebe; Gutiérrez Miranda, Claudia Elena; Marcelo Peña, José Luis; Kindt, Roeland; Atkinson, Rachel; Espinosa, Carlos Iván; Aguirre‐Mendoza, Zhofre; et al. (Wiley, 2020)
Understanding the vulnerability of tree species to anthropogenic threats is important for the efficient planning of restoration and conservation efforts. We quantified and compared the effects of future climate change and four current threats (fire, habitat conversion, overgrazing and overexploitation) on the 50 most common tree species of the tropical dry forests of northwestern Peru and southern Ecuador. We used an ensemble modelling approach to predict species distribution ranges, employed freely accessible spatial datasets to map threat exposures, and developed a trait‐based scoring approach to estimate species‐specific sensitivities, using differentiated trait weights in accordance with their expected importance in determining species sensitivities to specific threats. Species‐specific vulnerability maps were constructed from the product of the exposure maps and the sensitivity estimates. We found that all 50 species face considerable threats, with an average of 46% of species’ distribution ranges displaying high or very high vulnerability to at least one of the five threats. Our results suggest that current levels of habitat conversion, overexploitation and overgrazing pose larger threats to most of the studied species than climate change. We present a spatially explicit planning strategy for species‐specific restoration and conservation actions, proposing management interventions to focus on (a) in situ conservation of tree populations and seed collection for tree planting activities in areas with low vulnerability to climate change and current threats; (b) ex situ conservation or translocation of populations in areas with high climate change vulnerability; and (c) active planting or assisted regeneration in areas under high current threat vulnerability but low climate change vulnerability, provided that interventions are in place to lower threat pressure. We provide an online, user‐friendly tool to visualize both the vulnerability maps and the maps indicating priority restoration and conservation actions.